A remarkable new leaf-cutter bee from Thailand (Hymenoptera: Magachilidae). - Engel, Michael S.; Baker, Donald Burton (Contributions to Entomology = Beiträge zur Entomologie, 2006)
A remarkable new species of leaf-cutter bee, Megachile trichorhytisma Engel sp. n., is described and figured from two males collected in northern Thailand. The species is placed in a new subgenus, Aethomegachile Engel & Baker subgen. n., and is differentiated from previously known lineages of Megachile. Keywords Apoidea, Anthophila, Megachilinae, Megachilini, Southeast Asia, taxonomy. Nomenclatural Acts Aethomegachile Engel & Baker, 2006 (Megachile), sgen. n. trichorhytisma Engel, 2006 (Megachile (Aethomegachile)), spec. n.